BIOCHEMICAL AND HORMONAL RESPONSES OF MALVI AND NIMARI BULLOCKS OF MADHYA PRADESH TO WORK (Indian Journal of Animal Production and Management, 2013)
The study was conducted on six bullocks each of Malvi and Nimari breed maintained at Government cattle breeding farms located in their respective tract. For exercise bullocks were made to pull a load weight equivalent to 200 % of their body weight over a distance of 10 km on level road and ploughing of 200 meter level elliptical track was done continues for 2 hours. From each animal venous blood was collected just before and after carting and ploughing and the serum was separated out. The mean value of glucose, craetinine kinase, lactic acid, triiodothyronine (T3), thyroxine (T4), testosterone and cortisol before work were 61.27±0.43 mg/dl, 68.08±2.78 U/L, 98.64±3.12 mg/dl, 568.77±55.83 ng/dl, 2.28±0.89 mg/dl, 0.19±0.03 ng/ml and 10.95±2.10 mg/dl in Malvi bullocks and 66.95±0.96 mg/dl, 129.79±20.45 U/L, 280.21±7.74 mg/dl, 699.48±60.99 ng/dl, 12.33±2.86 mg/dl, 0.43±0.13 ng/ml and14.34±2.70 mg/dl in Nimari bullocks, respectively. Concentration of glucose, T3 and testosterone in blood decreased after work whereas, concentration of creatine kinase, lactic acid, T4 and cortisol increased after work in both breeds. The non significant changes in most of the parameters after work performance indicate that both Malvi and Nimari breeds are good draught breeds.
Keywords: Biochemical parameters; hormonal parameters; Malvi; Nimari